1994
DOI: 10.1007/bf00882773
|View full text |Cite
|
Sign up to set email alerts
|

Polar lipids and fatty acid composition ofThermus strains from New Zealand

Abstract: The polar lipids and fatty acid composition of Thermus aquaticus YT-1 and YS 041, T. filiformis Wai33 A1 and eighteen isolates from New Zealand, several of which are attributed to T. filiformis, were compared to complement the taxonomy of these organisms. The polar lipid patterns were essentially similar in all strains and consisted of one major phospholipid and one major glycolipid. The fatty acid analysis produced three basic groups corresponding to T. filiformis Wai33 A1, T. aquaticus and the third to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…For polar lipid analysis, lipids were extracted as described by Chung et al (2000). Individual polar lipids were separated by twodimensional TLC on silica gel 60 F 254 plates (Merck) as described by Ferraz et al (1994). For lipoquinone analysis, lipoquinones were extracted from freeze-dried cells and were purified as described by Tindall (1989).…”
mentioning
confidence: 99%
“…For polar lipid analysis, lipids were extracted as described by Chung et al (2000). Individual polar lipids were separated by twodimensional TLC on silica gel 60 F 254 plates (Merck) as described by Ferraz et al (1994). For lipoquinone analysis, lipoquinones were extracted from freeze-dried cells and were purified as described by Tindall (1989).…”
mentioning
confidence: 99%
“…NMR spectra were recorded in D 2 O (0.6 mL) with a Varian INOVA-500 spectrometer at 298 K with standard pulse sequences provided by Varian. Chemical shifts 1 H and 13 C were given in p.p.m. relative to HDO (4.75 p.p.m.)…”
Section: Nmr Analysismentioning
confidence: 99%
“…Those lipids are essential for the thermal stability and biological functions of the bacteria in extreme environments [9][10][11]. The polar lipids found in Thermus aquaticus, Thermus filiformis, Thermus scotoductus, and Thermus oshimai were mostly phospholipids and glycolipids [12], and the glycolipids from Thermus species examined thus far usually contain three hexoses, one N-hexosamine, and one glycerol [7,10,[12][13][14][15]. Although the sequences of those carbohydrate moieties have been studied by chemical and mass spectroscopic analysis, no complete structure is available as yet due to the lack of information on the linkages and configurations of the carbohydrate moiety.…”
mentioning
confidence: 99%
“…A minor glycolipid (glycolipid 2) and a minor aminophospholipid (phospholipid 1) are also produced by most strains. This polar lipid pattern can be considered a diagnostic chemotaxonomic characteristic of high-temperature Thermus strains since the only exception is found in T. scotuductus X-1 colony type 1; glycolipid 1 is not synthesized by this organisms, and glycolipid 2 is the predominant glycolipid (4,7,17,19,21,26). The polar lipid pattern of each low-temperature species consists of phospholipid 2 and two prominent glycolipids, designated glycolipids l a and lb, which are present in similar relative amounts, migrate close to each other, and are always detected (5,25).…”
mentioning
confidence: 99%
“…The amounts of the even-numbered is0 branched-chain fatty acids are generally relatively low compared with the amounts of the odd-numbered fatty acids, and branched-chain monounsaturated fatty acids are detected only when the organisms are grown at low temperatures (4,5,7,17,21,25,26). Hydroxy fatty acids were not detected in the early studies of the fatty acid compositions of Thermus species because the transmethylation methods used led to degradation of these compounds (7). However, recent results have shown that is0 3-hydroxy fatty acids (10 to 17% of the total fatty acids) are present in all of the strains assigned to T. aquaticus, while anteiso 3-hydroxy fatty acids (about 10% of the total fatty acids) are present in the type strain of T. filiformis (7, 15a (25).…”
mentioning
confidence: 99%